Linkages between EU Deforestation-Free Regulation and traceability tools: An exploration from the Honduran coffee sector - Melo-Velasco, Jenny; Padilla-Quiñonez, Claudina; Colindres, Mirian; Ceballos-Sierra, Federico; Wiegel, Jennifer (International Food Policy Research Institute, 2023)
Under the new EU deforestation regulation (EUDR), dated 31/05/2023, coffee producers and other producers of other significant commodities —cocoa, oil palm, rubber, soya, cattle, and wood— will have to comply with three aspects to export their products into the European Un ion. These aspects are i) Deforestation-free; 2) Production under the relevant legislation of the country of production; and 3) Due diligence statement. (Council of the European Union, 2022). These conditions are designed to minimize the European Union's impact on global deforestation and forest degradation, and to reduce its contribution to greenhouse gas emissions. Understanding this regulation, set to be enforced by December 30th, 2024, is crucial for coffee farmers who may face challenges due to the regulation's definition of deforestation, which includes forest-to-agroforestry conversion (Naranjo et al., 2023). For the Honduran coffee sector, where coffee is the primary agricultural export crop, with over 120,000 coffee farms making a significant contribution to a third of the agricultural GDP (IHCAFE, 2021), comprehending this regulation is essential. In examining the aspects of the EUDR, we encounter a complex interplay of definitions, ac tors, and processes that necessitate in-depth exploration to grasp their nuances and specific challenges. A transversal aspect involves how all the new information requested by this regulation is going to be collected, cleaned, integrated, stored, analyzed, reported, audited and updated. This paper aims to illuminate these processes by focusing on the existing and potential linkages among three traceability tools currently under development in the Honduran coffee sector.